Determination of Secondary Metabolites and Antioxidant Activity of Robusta Coffee Bean Ethanol Extract by UV-Vis Spectrophotometry - Tandi, Joni; Riani, Ni P. I.; Handayani, Tien W.; Kanan, Maria (Jurnal Akademika Kimia, 2023)
Robusta coffee beans (Coffea canephora Pierre ex.A.Froehner) have antioxidant, antidiabetic, and antihypertensive effects and can prevent coronary heart disease. This study aims to determine the compound content and total levels of secondary metabolites and to determine the antioxidant activity of robusta coffee bean extract. UV-Vis spectrophotometer was used to determine the total levels of secondary metabolites and antioxidant assay using DPPH reagent. The results obtained for the positive qualitative test contain secondary metabolites of alkaloids, flavonoids, saponins, and tannins and do not contain steroid compounds while for the quantitative test, the total alkaloid content is 0.1973% w/w (caffeine equivalent), flavonoids are 1.2106% w/w (equivalent to quercetin), saponins 0.536% w/w (equivalent to sapogenins), tannins at 9.7103% w/w (equivalent to tannic acid). The IC50 result for the antioxidant activity of the ethanolic extract of robusta coffee beans is 55.16 µg/mL which is included in the category of strong antioxidants.